Digital Crime Report Classification Management Through the Cekrekening.id System at the Ministry of Communication and Informatics - Lany Agustin; Suwanda, Bayu Suriaatmaja (Yayasan Sinergi Kawula Muda, 2025)
Digital financial activities in Indonesia have expanded rapidly and increased public dependence on online transactions across various platforms. The accelerated growth of digital services has improved efficiency and accessibility while exposing users to more complex forms of digital crime that include investment fraud, account impersonation, and phishing attempts. The government introduced the CekRekening.id platform to help the public verify and report bank accounts or e wallet numbers suspected of being involved in digital crime. This study examines the management of report classification within the platform and identifies operational challenges faced by the Electronic Transaction Complaint Services Team at the Ministry of Communication and Digital Affairs. The research was conducted through a three month internship that involved direct observation, active participation, and informal interviews with team members. The findings indicate that many users select inaccurate categories when submitting reports due to limited knowledge of digital crime types. Manual reclassification by the team becomes essential for maintaining verification accuracy but is hindered by incomplete narratives, insufficient evidence, and the absence of automated classification tools. The study highlights the importance of accurate categorization in strengthening case handling and supporting the identification of crime patterns. Recommendations include the integration of artificial intelligence, interface simplification, and improved digital literacy initiatives to enhance the overall effectiveness of the national digital crime reporting ecosystem.